Confirmation of the Need for Reclassification of Neisseria mucosa and Neisseria sicca Using Average Nucleotide Identity Blast and Phylogenetic Analysis of Whole-Genome Sequencing: Hinted by Clinical Misclassification of a Neisseria mucosa Strain - Jin, Yanqi; Xu, Hao; Yao, Qing; Gu, Beiqing; Wang, Zhouhan; Wang, Tianyuan; Yu, Xiaopeng; Lu, Yingfeng; Zheng, Beiwen; Zhang, Yimin (Frontiers in Microbiology, 2022)
The taxonomy of the genus Neisseria remains confusing, particularly regarding Neisseria mucosa (N. mucosa) and Neisseria sicca (N. sicca). In 2012, ribosomal multi-locus sequence typing (rMLST) reclassified both as N. mucosa, but data concerning 17 N. sicca strains remain available in GenBank. The continuous progress of high-throughput sequencing has facilitated ready accessibility of whole-genome data, which promotes vigorous development of average nucleotide identity (ANI) and high-resolution phylogenetic analysis. Here, we report that a Neisseria isolate, which caused native-valve endocarditis and multiple embolic brain infarcts in a patient with congenital heart disease, was misidentified as N. sicca by VITEK MS. This isolate was reclassified as N. mucosa by ANI Blast (ANIb) and by phylogenetic analysis using whole-genome data yielded by the PacBio Sequel and Illumina NovaSeq PE150 platforms. The confusion evident in the GenBank and matrix-assisted-laser desorption ionisation-time of flight mass spectrometry (MALDI-TOF MS) databases suggests that N. mucosa (n = 13) and N. sicca (n = 16) in GenBank should be reclassified using ANIb and high-resolution phylogenetic analysis. The whole-genome data of 30 strains（including the clinical isolate） were compared with the data of 27 type Neisseria strains (including one N. sicca and two N. mucosa type strains) as a genomic index. In total, 25 (8 originally identified as N. mucosa and 17 originally identified as N. sicca) and 7 (1 originally identified as N. sicca and 6 originally identified as N. mucosa) strains were re-classified into the N. mucosa and N. subflava groups, respectively; 1 residual N. mucosa strain was reclassified as Neisseria meningitidis. In conclusion, a combination of ANIb and robust phylogenetic analysis reclassified strains originally identified as N. mucosa and N. sicca into (principally) the N. mucosa group and the N. subflava group. The misclassified N. sicca and N. mucosa strains in the GenBank and MALDI-TOF MS databases were supposed to be corrected. Updated genomic classification strategy for originally identified N. mucosa and N. sicca strains was recommended to be adopted in GenBank.